2009
DOI: 10.1017/s0003055409990050
|View full text |Cite
|
Sign up to set email alerts
|

Gay Rights in the States: Public Opinion and Policy Responsiveness

Abstract: We study the effects of policy-specific public opinion on state adoption of policies affecting gays and lesbians, and the factors that condition this relationship. Using national surveys and advances in opinion estimation, we create new estimates of state-level support for eight policies, including civil unions and nondiscrimination laws. We differentiate between responsiveness to opinion and congruence with opinion majorities. We find a high degree of responsiveness, controlling for interest group pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
443
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 518 publications
(459 citation statements)
references
References 40 publications
14
443
0
2
Order By: Relevance
“…While these studies found evidence of responsiveness, results may be difficult to generalize (Burnstein 2003). These studies focus on highly salient morality policy issues, and, as Lax and Phillips (2009b) demonstrate, responsiveness to majority opinion is greatly enhanced by salience.…”
Section: Studies Of Responsivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…While these studies found evidence of responsiveness, results may be difficult to generalize (Burnstein 2003). These studies focus on highly salient morality policy issues, and, as Lax and Phillips (2009b) demonstrate, responsiveness to majority opinion is greatly enhanced by salience.…”
Section: Studies Of Responsivenessmentioning
confidence: 99%
“…For example, Gerber (1996Gerber ( , 1999 pools several national surveys to estimate state-level support for the death penalty and abortion restrictions; Lax and Phillips (2009b) estimate public support for eight policies regulating gay and lesbian rights; Lupia et al (2010) uses state polls to study state constitutional bans on same-sex marriage; and Norrander (2000) ties death penalty-specific opinion and policy. While these studies found evidence of responsiveness, results may be difficult to generalize (Burnstein 2003).…”
Section: Studies Of Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…study that identified, on a country-by-country basis, whether transsexual persons could change their sex on identity documents+ 45 The fact that the court considers these trends might mean that its judgments influence policy reforms in lagging states+ Nevertheless, it complicates causal inference, an issue we address at length in the empirical sections+ 40+ Transsexual marriage is a partial exception+ See 49 This leads us to hypothesize that ECtHR judgments increase the probability of policy change in countries where public support for such change is low and where domestic courts can rely on the convention and Strasbourg case law when exercising judicial review+ Legislative change. The most important factor facilitating legislative change is the partisan composition of governments+ The literature suggests that opposition to LGBT rights is greatest among religious, rural, and nationalist voters+ 50 Governments composed of parties supported by these voters should be less susceptible to the agenda-setting effect of ECtHR judgments favoring LGBT rights+ Conversely, the marginal effect of judgments should be greatest in countries where public acceptance of LGBT individuals is relatively low but where the executive is not from a party that relies on rural, religious, or nationalist constituencies+ A telling illustration is the 1999 Lustig-Prean judgment against the UK for banning gay men and lesbians from serving openly in the military+ LGBT activists and progressive political parties argued that similar bans in other CoE countries violated the European Convention+ In Germany, Winfried Stecher, a lieutenant dismissed after admitting his homosexuality at a public hearing, filed a court chal- 46+ Waaldijk 2001+ 47+ Foy -v Adamczyk and Pitt 2009;Inglehart and Baker 2000;and Lax and Philips 2009+ lenge to that country's "glass ceiling" policy that denied officer positions to gay men and lesbians+ 51 Defense Minister and Social Democrat~SPD! Rudolf Scharping vowed to fight the case, declaring homosexuals "unfit for leadership" in a leaked letter to fellow cabinet members+ 52 The coalition government~SPD and Green Party!…”
Section: Case Selectionmentioning
confidence: 99%
“…These minority stress processes have a negative effect on LGB mental and physical health (see Lick et al 2013 andMeyer &Frost, 2013 for reviews) and account for disparities in mental and physical health outcomes between LGB and heterosexual populations (e.g., Mays & Cochran, 2001). Although attitudes towards LGB people have improved drastically over the past two decades (e.g., Brewer, 2014;Lax & Phillips, 2009), LGB people continue to experience a multitude of minority stressors from family, co-workers, and other interpersonal and structural sources in their lives (Badgett, Lo, Sears, & Ho, 2007;Hatzenbuehler, 2014;Ryan, Huebner, Diaz, & Sanchez, 2009). …”
Section: The Importance Of Social Support In Lgb Communities: Perspecmentioning
confidence: 99%